Product recall management for Halal product - Zurina Shafii; Syahidawati Hj. Shahwan; Nurul Aini Muhamed; Hasnizam Hashim; Mohd. Fauzi Mohd. Amin; Alina Abdul Rahim; Aziz Y.A.; Jusoff K.; Zaib S.M.Z. (2024)
Indexed by Scopus